We Will Always Be Here : Native Peoples on Living and Thriving in the South - Bates, Denise E. (Other southerners., 2016)
The history of Native Americans in the U.S. South is a turbulent one, rife with conflict and inequality. Since the arrival of Spanish conquistadors in the fifteenth century, Native peoples have struggled to maintain their land, cultures, and ways of life. In We Will Always Be Here, contemporary tribal leaders, educators, and activists speak about their own experiences fighting for Indian identity, self-determination, cultural survival, and community development. This valuable collection portrays the lives of today's Southern Indians in their own words. Reflecting on such issues as poverty, education, racism, cultural preservation, and tribal sovereignty, the contributors to this volume offer a glimpse into the historical struggles of southern Native peoples, examine their present-day efforts, and share their hopes for the future. They also share examples of cultural practices that have either endured or been revitalized. In a country that still faces challenges to civil rights and misconceptions about Indian identity and tribal sovereignty, this timely book builds a deeper understanding of modern Native peoples within a region where they are often overlooked.